4K MODELI JÁRDEMINDE STUDENTLERDIŃ KOLLOBORATIV KOMPETENCIYASÍN RAWAJLANDÍRÍW STRATEGIYALARÍ - Seytjanova, U.K. (SCIENCE and SOCIETY, 2025)
The article analyzes research based on the 4K model. The importance and methods of applying collaborative educational technologies aimed at improving the professional qualifications of future primary education students are highlighted. Scientific conclusions on the topic are also presented.
Keywords: collaboration; 4C model; competency-based approach; communicative approach; creative approach; critical thinking; individual approach